The voyage of the Destiny - Nye, Robert, 1939- (Hamilton, 1982)
A fascinating fictional portrait of Sir Walter Raleigh follows the soldier, explorer, adventurer, and favorite of Queen Elizabeth of one final quest in search of gold, encountering Spanish forces, mutiny, court intrigue, disease, and pirates along the way and recalling his own storied rise from humble origins to the English court. [By publisher]